Geese mediate vegetation state changes with parallel effects on N cycling that leave nutritional legacies for offspring. Issue 8 (22nd August 2019) - Ruess, R. W.; McFarland, J. W.; Person, B.; Sedinger, J. S.
Abstract: Along the coastal fringe of the Yukon–Kuskokwim River Delta in southwestern Alaska, geese maintain grazing lawns dominated by a rhizomatous sedge that, when ungrazed, transitions to a taller, less palatable growth form that is taxonomically described as a different species. Nutrients recycled in goose feces, in conjunction with grazing, are critical to the rapid, nutritious growth of grazing lawns, and selective foraging on lawns has positive life‐history consequences for goslings. To examine whether bidirectional vegetation shifts were accompanied by parallel changes in N cycling, we studied how 15 N‐urea and 13 C 15 N‐glycine were processed through soils and plants of native and recently reverted vegetation states. Biomass and plant 15 N uptake from plots reverted to the tall growth form using exclosures and from those shifted to grazing lawns by experimental clipping and then goose grazing were identical to their native counterparts. Total recovery of 15 N within the tall vegetation types was significantly greater than within grazing lawns, although when expressed on a per‐gram biomass basis, percentage of 15 N recovery was significantly higher in grazing lawns compared with the tall vegetation state. Patterns of 13 C enrichment in CO2 soil efflux showed rapid use of 13 C‐glycine as a respiratory substrate within the first hour following injection, with both the timing and magnitude of efflux occurring at similar time points for all four vegetation types. However, higher soil respiration rates and a shorter half‐life for 13 C‐glycine in soils from tall meadows resulted in a greater proportional loss of 13 CO2 compared with grazing lawns. Despite daily‐to‐weekly tidal inundation, all of 15 N from labeled substrates could be accounted for within 1 m of the injection grid from soils of both states after 30 d, with significant levels of 15 N in soils and vegetation after one year. Geese have remarkably high fidelity to brood‐rearing areas, returning as adults to the same grazing lawns where they were raised as goslings. Our data suggest that the role fecal‐derived nutrients play in the positive feedback loop between geese and their food resources can provide a long‐term legacy that spans generations.